Beyond all reason : living with ideology in the university / Ronald Barnett. - Barnett, Ronald, 1947- (Open University Press, 2003)
In this title, Ronald Barnett argues that ideologies are now multiplying on campus and that, consequently, the university as a place of open debate and reason is in jeopardy. The book examines, as case studies, the ideologies of competition, quality, entrepreneurialism and managerialism.